PENGARUH PENGEMBANGAN KOMPETENSI SUMBER DAYA MANUSIA TERHADAP PRESTASI KERJA PEGAWAI PADA BADAN PENELITIAN DAN PENGEMBANGAN DAERAH KABUPATEN PANGKAJENE DAN KEPULAUAN - musawwir musawwir; Saban Echdar; Maryadi Maryadi (Jurnal Aplikasi Manajemen & Kewirausahaan MASSARO, 2021)
The study aims to determine and analyze the effect of HR competence consisting of knowledge, skills and attitudes partially and simultaneously on the work performance of employees at the Regional Research and Development Agency of Pangkajene and Kepulauan Regency, and the most dominant variable influencing employee performance at the Research and Development Agency Pangkajene and Kepulauan Regency. This research approach uses survey research. The research was carried out at the Regional Research and Development Agency of Pangkajene and Kepulauan Regency. The time of the study was conducted from September 2019 to November 2019. The population used in this study were all employees at the Regional Research and Development Agency of Pangkajene and Kepulauan Regency, amounting to 40 people. The results showed that HR competencies consisting of knowledge, skills and attitues partially and simultaneously on the work performance of employees at the Regional Research and Development Agency of Pangkajene and Islands Districts, as well as the most dominant knowledge variable influenced the employee performance at the Regional Research and Development Agency Pangkajene and Islands.